2015
DOI: 10.1007/s00737-015-0522-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between parental depressive symptoms and impaired bonding with the infant

Abstract: Impaired bonding with the infant is associated with maternal postpartum depression but has not been investigated extensively in fathers. The primary study aim was to evaluate associations between maternal and paternal depressive symptoms and impaired bonding with their infant. A secondary aim was to determine the associations between parents' marital problems and impaired bonding with the infant. The study is part of a population-based cohort project (UPPSAT) in Uppsala, Sweden. The Edinburgh Postnatal Depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
113
3
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 42 publications
14
113
3
4
Order By: Relevance
“…Furthermore, both paternal and All potential predictors' from Tables 2 and 3 with p-value < 0.2 included in the Logistic regression model. maternal depression can influence the behavioural development of the child (31); for example, they can lead to the increase in affective disorders and child development disorders (14,15). Therefore, this research shows the importance of prioritising the health of both the expectant fathers and mothers.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, both paternal and All potential predictors' from Tables 2 and 3 with p-value < 0.2 included in the Logistic regression model. maternal depression can influence the behavioural development of the child (31); for example, they can lead to the increase in affective disorders and child development disorders (14,15). Therefore, this research shows the importance of prioritising the health of both the expectant fathers and mothers.…”
Section: Discussionmentioning
confidence: 85%
“…Research has shown that paternal/partner depression affects children emotionally and behaviourally (14). Depressive fathers have impact on the bonding to the newborn child (15). Thomas et al (6) found that financial anxiety was also a stress factor for fathers during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Research example at our Department, Associate Professor Clara Aarts and research group. 5 Ill health and equality of care. Leadership and the organization of nursing care.…”
Section: Mental Health and Health Effects Of Migrationmentioning
confidence: 99%
“…It is important to distinguish this phenomenon from postpartum depression, even though the two are often associated in clinical samples [73,74], an association that may be exaggerated by the Berkson bias [75]. There is conflicting evidence for the association in the community [76,77,78,79,80,81,82,83].…”
Section: Definitionmentioning
confidence: 99%